2012
DOI: 10.1097/aln.0b013e31824674f6
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Epidural Analgesia and Traditional Pain Management Effects on Survival and Cancer Recurrence after Colectomy

Abstract: This large cohort study found that epidural use is associated with improved survival in patients with nonmetastatic colorectal cancer undergoing resection but does not support an association between epidural use and decreased cancer recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 46 publications
(37 reference statements)
4
84
2
3
Order By: Relevance
“…Although, the results of this meta-analysis are in line with previously published studies indicating an association between the use of epidural anesthesia and/or analgesia and improved shortand long-term OS; a recent study suggest in fact the opposite [16,18,20]. It has been suggested that regional anesthesia might improve the shortterm survival of patients by reducing pulmonary complications, decreasing deep venous thrombosis/pulmonary embolism and lowering rate blood transfusions; however, it remains less clear why the use of that anesthesia technique might reduce long-term mortality [16,20,[26][27].…”
Section: Discussionsupporting
confidence: 89%
“…Although, the results of this meta-analysis are in line with previously published studies indicating an association between the use of epidural anesthesia and/or analgesia and improved shortand long-term OS; a recent study suggest in fact the opposite [16,18,20]. It has been suggested that regional anesthesia might improve the shortterm survival of patients by reducing pulmonary complications, decreasing deep venous thrombosis/pulmonary embolism and lowering rate blood transfusions; however, it remains less clear why the use of that anesthesia technique might reduce long-term mortality [16,20,[26][27].…”
Section: Discussionsupporting
confidence: 89%
“…This approach may have led to LC underdetection. Of note, a recent analysis of SEER-Medicare data including cases diagnosed through 2005 evaluating outcomes after colorectal cancer resection found that laparoscopic cases comprised < 2% of cases [32]. Second, the unvalidated blood pints furnished variable may be undercoded and might not correlate with ICD-9-CM blood transfusion procedure codes [33].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The primary outcome of the study was time to discontinuation of opioids. This was defined as a period of thirty days without filling a prescription for an opioid after discharge from the hospital.…”
Section: Methodsmentioning
confidence: 99%